Photosynthetic performance and biochemical adjustments in two co-occurring Mediterranean evergreens, Quercus ilex and Arbutus unedo, differing in salt-exclusion ability - Fusaro, Lina; Mereu, Simone; Brunetti, Cecilia; Di Ferdinando, Martina; Ferrini, Francesco; Manes, Fausto; Salvatori, Elisabetta; Marzuoli, Riccardo; Gerosa, Giacomo; Tattini, Massimiliano (FUNCTIONAL PLANT BIOLOGY, 2014)
The responses to mild root zone salinity stress were investigated in two co-occurring Mediterranean woody evergreens, Quercus ilex L. and Arbutus unedo L., which differ in morpho-anatomical traits and strategies to cope with water deficit. The aim was to explore their strategies to allocate potentially toxic ions at organism level, and the consequential physiological and biochemical adjustments. Water and ionic relations, gas exchange and PSII performance, the concentration of photosynthetic pigments, and the activity of antioxidant defences, were measured. Q. ilex displayed a greater capacity to exclude Na+ and Cl- from the leaf than A. unedo, in part as a consequence of greater reductions in transpiration rates. Salt-induced reductions in CO2 assimilation resulted in Q. ilex suffering from excess of light to a greater extent than A. unedo. Consistently, in Q. ilex effective mechanisms of nonphotochemical quenching, also sustained by the lutein epoxide-lutein cycle, operated in response to salinity stress. Q. ilex also displayed a superior capacity to detoxify reactive oxygen species (ROS) than A. unedo. Our data suggest that the ability to exclude salt from actively growing shoot organs depends on the metabolic cost of sustaining leaf construction, i.e. species-specific leaf life-span, and the relative strategies to cope with salt-induced water stress. We discuss how contrasting abilities to restrict the entry and transport of salt in sensitive organs relates with species-specific salt tolerance.
Keywords: leaf longevity; net ion fluxes; salt tolerance; Stomatal conductance; violaxanthin-cycle pigments; water relations.

Gas exchange and JIP-test parameters of two Mediterranean maquis species are affected by sea spray and ozone interaction - Mereu, Simone; Gerosa, Giacomo; Marzuoli, Riccardo; Fusaro, Lina; Salvatori, Elisabetta; Finco, Angelo; Spano, Donatella; Manes, Fausto (Environmental and Experimental Botany, 2011)
Mediterranean maquis coastal ecosystems are subject to multiple oxidative stresses of both natural and anthropic origin, as sea spray, drought, high irradiance and ozone. In this article it is hypothesized that the interaction of ozone and sea spray is additive as a consequence of a higher reactive oxigen species accumulation. To test the hypothesis, an experiment was conducted in an Open Top Chambers facility where plants of Quercus ilex L. and Arbutus unedo L. were exposed to two levels of ozone and two levels of sea spray. The response of the species was evaluated by measurements of structural parameters (shoot growth and leaf biomass) and physiological parameters (leaf level gas exchange and chlorophyll a ﬂuorescence). The results contradict the hypothesis as the interaction of the two stresses is antagonistic on both species. The structure of both species was negatively affected by sea spray, however the two stresses combined allowed a higher growth and leaf area in A. unedo. The leaf level physiology of A. unedo was only moderately affected by the two stresses alone and in combined, while that of Q. ilex was altered to a further extent by sea spray and by its combination with ozone: photosynthesis and efﬁciency of the PSII was reduced by sea spray while the ratio of PSII to PSI was increased; the two stresses combined, instead, decreased the PSII to PSI ratio allowing for a higher photosynthesis. It is concluded that A. unedo is more resistant than Q. ilex to the two stresses alone and in combination, that ozone and sea spray interact antagonistically, and that the activity of PSI has a key role in the stress response
Keywords: Antagonistic interaction; dark respiration; JIP-test; OTC; Oxidative stress; PSI

Ozone stress in woody plants assessed with chlorophyll a fluorescence. A critical reassessment of existing data - Bussotti, Filippo; Desotgiu, Rosanna; Cascio, Chiara; Pollastrini, Martina; Gravano, Elisabetta; Gerosa, Giacomo; Marzuoli, Riccardo; Nali, Cristina; Lorenzini, Giacomo; Salvatori, Elisabetta; Manes, Fausto; Schaub, Marcus; et al. (Environmental and Experimental Botany, 2011)
This paper proposes an overall reassessment of results from ﬂuorescence transient (FT) and modulated ﬂuorescence (MF) analysis on tree species subjected to treatment with ozone. Findings from literature and open-top chamber experiments were used in this review, in order to identify damage mechanisms and repair/avoidance strategies. Main results are summarised below. (i) The most widely used parameter to assess the response to ozone treatment was the quantum yield of primary photochemistry in the dark-adapted state (ϕPo, or FV/FM). This parameter proved to be very stable in stress and control conditions. Ozone-induced stress – and the related loss of photosynthetic efﬁciency and performance – was characterized by the change occurring in all parameters connected with the controlled dissipation: reduction of FM, FV/FM, RC/CS0 (in the ﬂuorescence transient analysis) and NPQ (in theMF analysis). This can be considered as a down-regulationmechanism aimed at lowering the electron supply as a consequence of a reduced demand from the Calvin cycle. (ii) The FT analysis revealed a change in the I–P region shape, indicating that events beyond PSI are affected. These events include a lesser density of PSI itself and the compromised ability of the end acceptors of electrons (ferredoxine, NADP + ) and RuBP to manage effectively the ﬂux of electrons. This behaviour may create an imbalance between electrons sent by the electron transport chain and those reaching the acceptors beyond PSI. Free electrons (those coming from PSI, but that do not reach the end acceptors) can activate the oxygen from fundamental to excited status, with production of ROS (Reactive Oxygen Species), thus inducing photo-oxidation processes of the cellular content. (iii) In many cases a temporarily enhanced efﬁciency of electron trapping and transport (expressed by the parameters FV/FM, ET/TR, PIABS, pQ) in PSII system has been observed. That efﬁciency has been connected to the triggering of repair processes, but when it is connected to a reduced end acceptor capacity in combination with reduced Calvin cycle energy demand lead to over-excitation of the photosynthetic apparatus and initiates response towards visible foliar injury. (iv) The behaviour of F0 can help us distinguish between different response strategies. The increase of F0 observed in some ozone-treated plant species is considered an expression of irreversible damage in PSII, whereas lowered values of this parameter may indicate the activation of PSII in the cells surrounding the damaged one, as part of a compensative process. Future directions for the research in this ﬁeld concern: (i) the possibility to combine ﬂuorescence parameters with carbon assimilation and growth to support the study on critical levels and (ii) the analysis of the events concerning the activity of PSI and the events leading to the ﬁxation of CO2, by using innovative technologies
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Chlorophyll a fluorescence; OKJIP transient; Open top chambers; Ozone stress; Performance index; Quantum yield efficiency; Reaction centres; Visible foliar symptoms

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance

Physiological responses of Quercus ilex Leaves to Water Stress and Acute Ozone Exposure Under Controlled Conditions - Vitale, Marcello; Salvatori, Elisabetta; Loreto, Francesco; Fares, Silvano; Manes, Fausto (Water, Air, and Soil Pollution, 2007)
The combined effect of water stress and ozone (O3) on stomatal O3 flux, damage to photosynthesis, and detoxification by biogenic volatile organic compounds (BVOC) in Quercus ilex leaves was studied. A 4-weeks O3 exposure (250 ppb, 4 h per day) caused a reduction of photosynthesis and stomatal conductance, which was fully recovered 1 week after the end of the treatment, in well-watered and water-stressed plants. Measurements of stomatal O3 flux revealed a low stomatal flux of the pollutant, which became minimal after stomatal closure caused by water stress. An induction of volatile monoterpenes, important compounds in the O3 scavenging system in Q. ilex, and a burst of lipoxygenase compounds (LOX), which are released as gaseous by-products of membrane peroxidation, was observed after 2–3 weeks of O3 fumigation. However, these compounds were also released in control leaves that were exposed to ozone only briefly, to determine stomatal O3 flux. The low stomatal flux that occurred in water stress conditions helped avoiding permanent damage to Q. ilex leaves, although during the O3 treatment photosynthesis was severely limited by stomatal closure. In well-watered plants, O3 fumigation caused a noticeable increase of nocturnal stomatal conductance. If confirmed on adult plants under field conditions, this effect can imply larger flux of O3 at night and possible detrimental effects of O3 on leaf functions in plants exposed to high nocturnal O3 levels.
Keywords: Gas exchange; Holm oak (Quercus ilex); lipoxygenase products; monoterpene emission; o3 flux; photosynthesis; Stomatal conductance